2022
DOI: 10.1371/journal.pgph.0000742
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and confidence in the Philippines and Malaysia: A cross-sectional study of sociodemographic factors and digital health literacy

Abstract: With the emergence of the highly transmissible Omicron variant, large-scale vaccination coverage is crucial to the national and global pandemic response, especially in populous Southeast Asian countries such as the Philippines and Malaysia where new information is often received digitally. The main aims of this research were to determine levels of hesitancy and confidence in COVID-19 vaccines among general adults in the Philippines and Malaysia, and to identify individual, behavioural, or environmental predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…However, the sudden and unpredictable nature of such crises can lead to fluctuations in vaccine acceptance. This is attributed to asymmetrical information regarding vaccines, where initial misinformation or incomplete knowledge may foster misunderstandings and resistance towards vaccination, fueling panic and distrust 37 . Yet, as validation of vaccine safety increases, public acceptance gradually improves.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sudden and unpredictable nature of such crises can lead to fluctuations in vaccine acceptance. This is attributed to asymmetrical information regarding vaccines, where initial misinformation or incomplete knowledge may foster misunderstandings and resistance towards vaccination, fueling panic and distrust 37 . Yet, as validation of vaccine safety increases, public acceptance gradually improves.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these demographic findings, other studies have reported increased vaccination hesitancy among females, urban populations, and individuals with higher education. Therefore, health promotion efforts should be directed towards the general population to address these concerns [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than one hundred children died in the Philippines as a consequence of the Dengvaxia scandal, resulting from the inappropriate administration of vaccines against Dengue fever. 26, 27 Prior studies found that low-risk perception of COVID-19 and concerns over vaccine safety and side effects are highly in uential barriers for parents in vaccinating their children. [41][42][43] Furthermore, recent studies observed that social media information has a growing impact on the vaccination choices of mothers and women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 For example, in the Philippines, where more than a hundred children died from the side effects of a Sano Pasteur vaccine against Dengue fever, Dengvaxia, which was especially dangerous for children who had never been infected with Dengue, 26 vaccine hesitancy is likely to be strongly associated with parents and females. 27 As another example, widespread distrust in the central government exists in the society of Papua New Guinea (PNG), which consists of thousands of tribes commanded by big men or chiefs. 28 Under such circumstances, it is di cult to disseminate reliable information about COVID-19, and compliance with health recommendations from the government may be extremely low.…”
Section: Introductionmentioning
confidence: 99%